2016
DOI: 10.1038/srep34074
|View full text |Cite
|
Sign up to set email alerts
|

Coalescence of Immiscible Liquid Metal Drop on Graphene

Abstract: Molecular dynamics simulations were performed to investigate the wetting and coalescence of liquid Al and Pb drops on four carbon-based substrates. We highlight the importance of the microstructure and surface topography of substrates in the coalescence process. Our results show that the effect of substrate on coalescence is achieved by changing the wettability of the Pb metal. Additionally, we determine the critical distance between nonadjacent Al and Pb films required for coalescence. These findings improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 46 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…Since the differences between conventional flat superhydrophobic surfaces and textured superhydrophobic surfaces lie in the existence of textures, their layout should significantly affect the wall wetting behavior and hence droplet dynamics. Shi et al showed that droplet jumping could be promoted by increasing the texture height or decreasing their spacing . Gao et al performed molecular dynamics simulations and showed that nanodroplets prefer to jump away from those surfaces with decreased surface wettability intensity and solid fraction .…”
Section: Introductionmentioning
confidence: 99%
“…Since the differences between conventional flat superhydrophobic surfaces and textured superhydrophobic surfaces lie in the existence of textures, their layout should significantly affect the wall wetting behavior and hence droplet dynamics. Shi et al showed that droplet jumping could be promoted by increasing the texture height or decreasing their spacing . Gao et al performed molecular dynamics simulations and showed that nanodroplets prefer to jump away from those surfaces with decreased surface wettability intensity and solid fraction .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that metal and carbon can only form soft bonds via the charge transfer, we use the 12-6 Lennard-Jones (L-J) potential to calculate the Pb–C interaction, which is given as where ε is the depth of the potential wall, σ is the finite distance at which the interparticle potential is zero, and r c is the cutoff distance of 10.0 Å. The related parameters are ε Pb–C = 0.01751 eV and σ Pb–C = 3.288 Å. …”
Section: Models and Methodsmentioning
confidence: 99%
“…Gao et al considered that the surface texture structure changed the wetting state of droplets and affected the coalescence-jumping dynamic (Figure c) . When the bottom of the droplet entered the texture structure exhibiting the Wenzel state or the partial wetting state, the droplet was inhibited from leaving the substrate surface. , In addition, some researchers have explained the influence of the microcylinder geometrical parameters on the contact angle of the droplet. Wang et al reported that the static contact angle increased nonlinearly with the increase in the distance of the microcolumn array (Figure d) .…”
Section: Effect Of Superhydrophobic Structurementioning
confidence: 99%